2009
DOI: 10.1172/jci37563
|View full text |Cite
|
Sign up to set email alerts
|

Children with obsessive-compulsive disorder: are they just “little adults”?

Abstract: Childhood-onset obsessive-compulsive disorder (OCD) affects 1%-2% of children and adolescents. It is characterized by recurrent obsessions and compulsions that create distress and interfere with daily life. The symptoms reported by children are similar to those seen among individuals who develop OCD in adulthood, and the two groups of patients are treated with similar symptom-relieving behavior therapies and medications. However, there are differences in sex ratios, patterns of comorbidity, and the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 114 publications
0
65
0
14
Order By: Relevance
“…The basis of diagnosis is likely to be completely reformulated to consider biological information, such as genetics and imaging data. And just as we no longer use psychoanalysis for peptic ulcer disease, treatments such as antibiotics and deep brain stimulation are likely to replace current medications as we learn more about the pathophysiology of disorders, such as one form of childhood-onset OCD and depression (2,4). In a commencement speech given at Morehouse College in 1959, Martin Luther King Jr. reflected on the Rip Van Winkle story and the tragedy that this fictional character had slept through the most important revolution in American history (56).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The basis of diagnosis is likely to be completely reformulated to consider biological information, such as genetics and imaging data. And just as we no longer use psychoanalysis for peptic ulcer disease, treatments such as antibiotics and deep brain stimulation are likely to replace current medications as we learn more about the pathophysiology of disorders, such as one form of childhood-onset OCD and depression (2,4). In a commencement speech given at Morehouse College in 1959, Martin Luther King Jr. reflected on the Rip Van Winkle story and the tragedy that this fictional character had slept through the most important revolution in American history (56).…”
Section: Discussionmentioning
confidence: 99%
“…The present series, "Rethinking Mental Disorders," introduces several of the front lines of this revolution. It may be notable that this revolution is infused by new ideas from outside psychiatry: the authors include a neurologist (2), a developmental neuroscientist (5), and a pediatrician (4). In this overview, I describe four conceptual shifts, or disruptive insights, that provide the intellectual basis of this revolution.…”
Section: Public Health Significance Of Mental Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaira and Swedo [4] outlined patterns of comorbidity and related neuroimaging studies in children with obsessive-compulsive disorder. They pointed out that two decades of research had indicated that childhood OCD is also thought to be associated with dysfunction of cortico-striato-thalamo-cortical circuitry (Swedo, Rapoport , Leonard, Lenane & Cheslow) [5] .…”
Section: Obsessive Compulsive (Pandas) Disordermentioning
confidence: 99%
“…Regional autoimmune reactors are suggested by the demonstration that monoclonal antibodies specific for mammalian lysoganglioside and N-acetyl-B-glucosamine, an epitope of group A streptococci". According to Kaira and Swedo [4] introduction of these antibodies into basal ganglia of rats has been shown to produce stereotypies such as "wood-chip eating, self-gnawing, biting, licking and grooming, paw to mouth movements, vacuous chewing and head and paw shaking".…”
Section: Obsessive Compulsive (Pandas) Disordermentioning
confidence: 99%